In situ metal–organic framework-derived c-doped Ni3S4/Ni2P hybrid co-catalysts for photocatalytic H2 production over g-C3N4 via dye sensitization. (21st June 2019) - Qi, Yinhong; Xu, Jixiang; Zhang, Mingjuan; Lin, Haifeng; Wang, Lei
Abstract: Controlled integration of metal-based sulfides with phosphides possessing strong coupling effects is a promising way to accelerate electron transfer by modulating the electronic structures of the host species. In this work, a c-doped Ni3 S4 /Ni2 P (C@Ni3 S4 /Ni2 P) hybrid co-catalyst produced by in situ sulfuration and phosphidation of Ni-MOF was decorated on g-C3 N4 and subsequently used for photocatalytic H2 evolution under visible-light irradiation. Among the prepared composites tested herein, the optimized g-C3 N4 /C@Ni3 S4 /Ni2 P-30 composite showed the highest H2 evolution rate (14.49 mmol g −1 h −1 ) with 1.0 mmol L −1 of Eosin Y (EY)-sensitization, which is 10 times higher than that of pristine g-C3 N4 (1.33 mmol g −1 h −1 ). The enhanced photocatalytic activity of this composite can be attributed to: (i) electronic interactions between Ni2 P and Ni3 S4 (which synergistically increased the electron transfer rate) and (ii) staggered band alignment of excited-stated EY, g-C3 N4, Ni3 S4, and Ni2 P. This work may provide some perspectives for utilization of MOF-derived hybrid co-catalysts as substitutes of noble metals for effective photocatalytic H2 evolution. Highlights: g-C3 N4 modified by Ni-MOF-derived C@Ni3 S4 /Ni2 P cocatalyst was used to generate H2 . Electronic interactions between Ni2 P and Ni3 S4 accelerate electron transfer. The optimal H2 -evolution rate is14.49 mmol g −1 h −1 under Eosin Y-sensitization. Staggered band, synergistic effect of Ni2 P and Ni3 S4 are responsible for enhance.